The Clinical Value of Pulmonary Rehabilitation in Reducing Postoperative Complications and Mortality of Lung Cancer Resection: A Systematic Review and Meta-Analysis - Mao, Xiaowei; Ni, Yiqian; Niu, Yanjie; Jiang, Liyan (Frontiers in Surgery, 2021)
Background: Pulmonary rehabilitation was one meaningful way for improving exercise tolerance and pulmonary function. Thus, it may reduce the postoperative complications and mortality of pulmonary resection. Hence, we refreshed date and conducted this systemic analysis. Method: We searched the Pubmed, Web of Science and EMBASE with the mesh “lung OR pulmonary” AND “operation OR resection OR surgery” AND “rehabilitation or exercise”. The cut-off date was September 30th, 2020. The publications were filtrated and date were extracted. Data were extracted from all selected studies by two reviewers. The Review Manger 5.1 and the fixed or random regression model was used for calculating the pooled odds ratio (OR). Result: Finally, 13 publications were enrolled in this study. Among them, 5 publications reported the mortality, 9 reported the postoperative complications, and 7 reported the postoperative pulmonary complications. The pooled OR of mortality was 1.32(95% confidence interval (CI): 0.54-3.23) for pulmonary rehabilitation group, the pooled OR of postoperative complications was 0.64(95% CI: 0.50-0.81) for pulmonary rehabilitation group, the pooled OR of postoperative pulmonary complications was 0.52 (95% CI: 0.29-0.93) for pulmonary rehabilitation group. Subgroup analysis revealed the perioperative pulmonary rehabilitation was the most important part. Conclusion: The pulmonary rehabilitation may not affect the mortality of pulmonary resection patients, however it could decrease the postoperative complications, especially the pulmonary complications. Perioperative pulmonary rehabilitation was the most important part of the program.